Biosorption of Heavy Metals and Nutrients: A Green Approach for Clean-Up of Contaminated Water - Ismail; Znad, Hussein (Nova Science Publishers, 2015)
Biosorption is a physiochemical process which allows the biomass to passively concentrate and bind contaminants onto its cellular structure. Though using the biomass in polluted water treatment and environmental clean-up has attracted scientists and engineers since this phenomenon will provide an economical green alternative for treatment of industrial wastewater and aid in environmental remediation. However, an extensive research work in this regard has found that a wide variety of commonly discarded waste including eggshells, bones, peat, fungi, seaweed, yeast, and carrot peels can efficiently remove harmful toxic heavy metal from polluted water. Research work was extended for novel applications of giant reed, and corncob residues for excessive ammonium removal from contaminated water. Biosorption may be used as an environmentally friendly filtering technique. There is no doubt that the world could benefit from more rigorous filtering of harmful pollutants created by industrial processes and all-around human activities. Removal of contaminants accomplished with biosorption is an alternative to using man-made costly ion exchange resins, due to the fact that biosorbents are often waste from farms or they are very easy to regenerate. This chapter will cover the comprehensive understanding and advancement of biomaterials applications for removal of pollutants from water.